Two new species of Dactylogyridae (Monogenoidea) on rose spotted snapper, Lutjanus guttatus (Osteichthyes: Lutjanidae), from the coasts of Nayarit and Sinaloa, Mexico - García-Vargas, Fernando; Fajer-Ávila, Emma J.; Lamothe-Argumedo, M. Rafael. (Zootaxa, 2008)
Two new species, one each in Haliotrema and Euryhaliotrema, from the gills of the rose spotted snapper, Lutjanus guttatus, Steindachner, 1869, in Nayarit and Sinaloa, northwestern coast of Mexico, are described. Haliotrema guttati n. sp. is differentiated from its congeners H. longihamus and H. heteracantha by the presence of a delicate membranous envelope at the base of the copulatory organ, ventral and dorsal anchors with a prominent bulge on the inner face of the shaft, the base of the dorsal anchors simply fenestrated, ventral and dorsal bars having wide ends, and the ventral and dorsal bars W-shaped. Euryhaliotrema perezponcei n. sp. is characterized by a coiled male copulatory organ with three counterclockwise rings.